Development of a poststroke checklist to standardize follow-up care for stroke survivors - Philp, Ian; Brainin, Michael; Walker, Marion F.; Ward, Anthony B.; Gillard, Patrick; Shields, Alan L.; Norrving, Bo (W.B. Saunders, 2013)
Background: Long-termcare for stroke survivors is fragmented and lacks an evidence-based, easy-to-use tool to identify persistent long-term problems among stroke survivors and streamline referral for treatment. We sought to develop a poststroke checklist (PSC) to help health care professionals identify poststroke problems amenable to treatment and subsequent referral. Methods: An instrument development team, supported by measurement experts, international stroke experts, and poststroke care stakeholders, was created to develop a long-term PSC. A list of long-term poststroke problem areas was generated by an international, multidisciplinary group of stroke experts, the Global Stroke Community Advisory Panel. Using Delphi methods, a consensus was reached on which problem areas on the list were most important and relevant to include in a PSC. The instrument development team concurrently created the actual checklist, which provided example language about how to ask about poststroke problem areas and linked patient responses to a specific referral process. Results: Eleven long-term poststroke problem areas were rated highly and consistently among stroke experts participating in the Delphi process (n = 12): secondary prevention, activities of daily living, mobility, spasticity, pain, incontinence, communication, mood, cognition, life after stroke, and relationship with caregiver. These problem areas were included in the long-term PSC. Conclusions: The PSC was developed to be a brief and easy-to-use tool, intended to facilitate a standardized approach for health care providers to identify long-term problems in stroke survivors and to facilitate appropriate referrals for treatment.